RBC Parameters in Patients of Systemic Lupus Erythematosus Report of 75 Cases from Lahore, Pakistan - MUHAMMAD USMAN, ATIYA MAHBOOB, ASMA MUNIR, MONA AZIZ, MANAAL AFZAAL (Journal of Fatima Jinnah Medical University, 2018)
Background: Systemic Lupus Erythematosus (SLE) is a multisystem autoimmune disease that may virtually affect every organ in the body. It is characterized by the production of a variety of autoantibodies. Haematological manifestations of SLE are diverse. Anemia is the major haematologic manifestations of SLE . Objectives: To determine the various RBC parameters in patients of Systemic Lupus Erythematosus . Design: Prospective, cross sectional. Place and duration of study: Department of Haematology, PGMI/Shaikh Zayed Hospital, Lahore from May 2011 to April 2012. Patients and Methods: Seventy five diagnosed cases of SLE fulfilling the inclusion criteria presenting to the medical in- and out-patient departments of Shaikh Zayed Medical complex Lahore, were included in the study. Written informed consent was taken. Patients were investigated in Haematology Laboratory, Shaikh Zayed Medical complex, Lahore. All collected information was entered into SPSS version 17.0 and analyzed using its statistical package. Results: There were 65 (86.7%) females and 10 (13.3%) male patients. Female to male ratio was 6.5:1. Age ranged from 15 to 65 years (Mean age 29.49±11.7 years). Anemia was seen in 74 patients (98.67%). Mean Hb was 8.45±1.95 g/dl (range 4.2-13.0 g/dl). Mean RBC count was 3.45x1012±0.93/l (range 1.15-5.52x1012/l. Mean Hematocrit was 26.92±7.17% (range 12.19-43.27%).Value of MCV ranged from 51-115fl (mean MCV 78.5±9.98 fl). Similarly mean MCH was 25.19±4.19pg (range 14.7-44.7 pg), while mean MCHC came out to be 31.6±2.53g/dl (range 26-42g/dl) . Conclusion: All RBC parameters were disturbed to a variable range in patients with SLE in the study cases. Complete haematological examination should be carried out in every patient of SLE in early course of the disease for proper management and prevention of morbidity associated with anemia.